2015
DOI: 10.3855/jidc.6035
|View full text |Cite
|
Sign up to set email alerts
|

Association between Helicobacter pylori infection and overweight or obesity in a Chinese population

Abstract: Introduction: Recent studies found that Helicobacter pylori (H. pylori) infection plays a role in cardiometabolic disorders. The objective of this study was to assess the association between H. pylori infection and overweight or obesity in a Chinese population. Methodology: A cross-sectional analysis using data from the subjects who underwent a health examination between January 2010 and June 2012 in the department of comprehensive medicine was performed. Diagnosis of H. pylori infection was achieved using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
3
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 36 publications
0
30
3
4
Order By: Relevance
“…In our study, the H. pylori infection appeared to be a protective factor for obesity. The H. pylori (+) subjects had decreased BMI more than H. pylori (-) subjects, although the differences were not significant, which is opposite to the result of the cross-sectional study by Zhang et al[15]. This contrary finding may be attributed to different populations being analyzed and/or the different methods used to make the diagnosis.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…In our study, the H. pylori infection appeared to be a protective factor for obesity. The H. pylori (+) subjects had decreased BMI more than H. pylori (-) subjects, although the differences were not significant, which is opposite to the result of the cross-sectional study by Zhang et al[15]. This contrary finding may be attributed to different populations being analyzed and/or the different methods used to make the diagnosis.…”
Section: Discussioncontrasting
confidence: 77%
“…A meta-analysis of 18 observational studies including 10000 subjects found a higher body mass index among H. pylori -positive subjects compared with H. pylori -negative subjects[14]. A cross-sectional study showed that H. pylori infection was significantly and positively associated with overweight/obesity in a Chinese population[15]. Reports from different areas and countries were not consistent with each other, and most were cross-sectional studies.…”
Section: Introductionmentioning
confidence: 99%
“…El análisis inicial de nuestro estudio mostró una mayor prevalencia de sobrepeso, obesidad, hipertensión arterial, diabetes mellitus y síndrome metabólico en los pacientes con dispepsia infectados por la bacteria. Algunos estudios han encontrado que esta bacteria desempeña un papel importante en los trastornos cardiometabólicos y recientemente su presencia se ha asociado en forma significativa y consistente con mayor índice de masa corporal, sobrepeso y obesidad en la población China 22,23 . Sin embargo, esta relación no es clara pues otros estudios han demostrado una relación inversa entre la infección por la bacteria y la prevalencia de sobrepeso y obesidad tanto en niños como en adultos de países desarrollados 24,25 .…”
Section: Discussionunclassified
“…Besides that higher BMI potentiates impaired glucose tolerance in adults [23]. It is early to say if BMI can be affected by Hp seopositivity but the latest data show that this is possible [24].…”
Section: Metabolic Changes In Hp With T2dmmentioning
confidence: 99%